The MAP kinase JNK2 mediates cigarette smoke-induced arterial thrombosis - Breitenstein, Alexander; Stämpfli, Simon F.; Reiner, Martin F.; Shi, Yi; Keller, Stephan; Akhmedov, Alexander; Clerigué, Ariane Schaub; Spescha, Remo D.; Beer, Hans-Jürg; Lüscher, Thomas F.; Tanner, Felix C.; Camici, Giovanni G. (Thrombosis and Haemostasis, 2017)
Despite public awareness of its deleterious effects, smoking remains a major cause of death. Indeed, it is a risk factor for atherothrombotic complications and in line with this, the introduction of smoking ban in public areas reduced smoking-associated cardiovascular complications. Nonetheless, smoking remains a major concern, and molecular mechanisms by which it causes cardiovascular disease are not known. Peripheral blood monocytes from healthy smokers displayed increased JNK2 and tissue factor (TF) gene expression compared to non-smokers (n=15, p<0.05). Similarly, human aortic endothelial cells exposed to cigarette smoke total particulate matter (CS-TPM) revealed increased TF expression mediated by JNK2 (n=4; p<0.05). Wild-type and JNK2−/− mice were exposed to cigarette smoke for two weeks after which arterial thrombosis was investigated. Wild-type mice exposed to smoke displayed reduced time to thrombotic arterial occlusion (n=8; p<0.05) and increased tissue factor activity (n=7; p<0.05) as compared to wild-type controls (n=6), while JNK2−/− mice exposed to smoke maintained an unaltered thrombotic potential (n=8; p=NS) and tissue factor activity (n=8) comparable to that of JNK2−/− and wild-type controls (n=6; p=NS). Smoking caused an increased production of reactive oxygen species (ROS) in wild-type but not in JNK2−/− mice (n=7; p<0.05 for wild-type mice and n=5–6; p=NS for JNK2−/− mice). In conclusion, the MAP kinase JNK2 mediates cigarette smoke-induced TF activation, arterial thrombosis and ROS production. These results underscore a major role of JNK2 in smoke-mediated thrombus formation and may offer an attractive target to prevent smoke-related thrombosis in those subjects which do not manage quitting.
Keywords: Thrombosis; animal model; tissue factor